Analysis of the Implementation of Driving License Type D (SIM D) Issuance for Persons with Disabilities in Indonesia - Anita Octaria Tambun; Ima Mayasari (Lembaga Bale Literasi, 2026)
This study aims to analyze the implementation of the issuance of Driving License Type D (SIM D) for persons with disabilities in Indonesia as part of efforts to promote inclusive public service delivery. SIM D functions not only as a legal authorization for driving but also as an instrument for fulfilling mobility rights and empowering persons with disabilities. This research adopts a qualitative approach using a literature review method, drawing on various scholarly sources, regulatory frameworks, and policy documents related to disability and public service provision. The findings indicate that, normatively, the SIM D policy is supported by a strong legal foundation and reflects the state’s commitment to the principle of equality. However, its implementation in practice faces multidimensional challenges, including limited accessible infrastructure, insufficient human resource capacity, weak policy communication, and suboptimal institutional coordination. In addition, social factors such as stigma toward persons with disabilities further influence the effectiveness of policy implementation. This study underscores the need for comprehensive improvement strategies through strengthening policy communication, ensuring equitable resource distribution, enhancing implementers’ capacity, and applying universal design principles in public services. The findings contribute to the development of more inclusive transportation policies and the improvement of service quality for persons with disabilities in Indonesia.